If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12-6k=6(1+3k)
We move all terms to the left:
-12-6k-(6(1+3k))=0
We add all the numbers together, and all the variables
-6k-(6(3k+1))-12=0
We calculate terms in parentheses: -(6(3k+1)), so:We get rid of parentheses
6(3k+1)
We multiply parentheses
18k+6
Back to the equation:
-(18k+6)
-6k-18k-6-12=0
We add all the numbers together, and all the variables
-24k-18=0
We move all terms containing k to the left, all other terms to the right
-24k=18
k=18/-24
k=-3/4
| 8t^2-18=0 | | 2.3+10m=7.47 | | 5x-9x-11=-4x+9-11 | | 6-c=2-5(2c-7) | | 3z+1=z+2 | | 0.5x-1.9=3.8x+2.9 | | g-13/4=( | | 7r-5(6-3r)=-184 | | 5(2x+8)=-23+53 | | 11x=15x+16 | | 33=-7+5x | | -19+p=5(7-5p)-2 | | 18a-9a=9 | | 4(5x+8)=-44+36 | | 7t+35+(10.5-+t)=308 | | 3x-11+x7=180 | | 5h-4=26 | | 8x+78+2x+114=90 | | (5/8x+61/4)-10=0 | | N2-5n=0 | | 8r+8=4(r+6) | | 18.10x+183.75=14.59(x+15) | | (x-100)/(x)=0.8 | | 10-8(2x+4)=10 | | 18.10x+183.75=14.59(x+15 | | (2x+29)=(9x-13) | | -2-n=7+2n | | 312+3x=340 | | 3x+5x-9=2(4x+1) | | y=17-4(4) | | (x-100)/x=0.8 | | 5x+3+7x=14x-19 |